2003
DOI: 10.1016/s0885-3924(02)00686-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Patient Perception of the Helpfulness of a Prompt Sheet Versus a General Information Sheet During Outpatient Consultation

Abstract: The purpose of this study was to determine the helpfulness of a prompt sheet versus a general information sheet for patient communication with physicians. Sixty women with breast cancer attending their first outpatient consultation with a breast medical oncologist were randomized to receive either a prompt sheet (PS) or a general information (GI) sheet regarding breast cancer. Analysis of the results found that helpfulness of the written material was rated higher in the PS group (8.5 +/- 2) than the GI group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 12 publications
2
124
1
Order By: Relevance
“…This was particularly telling with the item 'Fear of Recurrence'. Intervention with communication strategies and adjuncts e.g., writing down questions, use of computer-assisted education package and prompt sheets (Brown et al, 2001;Bruera et al, 2005;Davison and Degner, 2002), can activate cancer patients into being better communicators (e.g., express concerns, ask questions, being assertive, etc.) but the effectiveness of such interventions depends, in part, on physician/ clinician endorsement (Parker et al, 2005;Street et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly telling with the item 'Fear of Recurrence'. Intervention with communication strategies and adjuncts e.g., writing down questions, use of computer-assisted education package and prompt sheets (Brown et al, 2001;Bruera et al, 2005;Davison and Degner, 2002), can activate cancer patients into being better communicators (e.g., express concerns, ask questions, being assertive, etc.) but the effectiveness of such interventions depends, in part, on physician/ clinician endorsement (Parker et al, 2005;Street et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[13] QPLs have been developed for patients seeing medical oncologists, radiation oncologists or surgeons for the first time, [14,15] and patients and carers newly referred to palliative care. [16] No QPL has been developed for patients with advanced cancer outside the palliative care setting.…”
Section: Introductionmentioning
confidence: 99%
“…Models of physician-patient communication have suggested that in order for physicians to adequately assess and respond to patients' differing needs, physicians must involve patients in the medical consultation. On the most simplistic level, patients who take an active role in the medical consultation have an opportunity to ask questions and can elicit the information that is most important to them [10,11]. Frequently, however, patients may be unable to conceptualize or articulate their questions, requiring physicians not only to allow their patients to participate in the consultation, but also to actively elicit and explore patients' thoughts, feelings, ideas, and concerns, in order to gain insight into the patient's perspective.…”
Section: Introductionmentioning
confidence: 99%